Determining the Effects of Manganese Source and Level on Growth Performance, Carcass Characteristics, and Economics of Growing-Finishing Pigs - H. R. Kerkaert; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 1,944 mixed sex growing-finishing pigs (PIC; 337 × 1050; initially 76.0 ± 3.71 lb) were used in a 107-d growth trial to determine the effects of increasing levels of two different manganese sources on the performance of growing-finishing pigs from 76 to 295 lb. Pens were assigned to 1 of 6 treatments in a randomized complete block design with initial weight as a blocking factor. There were 12 replicate pens per treatment and 27 pigs per pen. The experimental diets were corn-soybean meal-based and were fed in 4 phases. The 6 dietary treatments were arranged in a 2 × 3 factorial with main effects of Mn source, (MnSO4or Mn hydroxychloride: IBM), and 3 added Mn concentrations (8, 16, or 32 ppm). The trace mineral premix was formulated to contain no added Mn. There were no Mn source × level interactions (P>0.10) observed for any of the individual dietary phases. For the overall period (d 0 to 107), there was a Mn source × level interaction (quadratic,P= 0.048) for feed efficiency (F/G), with F/G improving for the lowest and highest level of Mn supplementation from IntelliBond M (IBM) whereas F/G tended to improve with increasing Mn from MnSO4. For the main effect of level, the intermediate dietary level of Mn had the poorest (quadratic,P<0.097) average daily gain (ADG) in phases 1 and 4, which resulted in the poorest overall ADG and final body weight (BW) (quadratic,P<0.05). There was no evidence for differences in pigs fed either Mn source for ADG or ADFI. There was a tendency for Mn source × level interaction (quadratic,P= 0.075) for carcass yield, where yield did not change by added MnSO4, but increased then decreased for pigs fed diets with IBM. Loin depth increased (linear,P= 0.035) for pigs fed increasing amounts of Mn from MnSO4but decreased when Mn was increased from IBM. Pigs fed the intermediate level of Mn also had the lightest HCW (quadratic,P= 0.071) and decreased loin depth (quadratic,P= 0.044). No differences were observed in economics except for revenue (quadratic,P= 0.093) being the lowest for pigs fed the intermediate level of Mn. No evidence of difference (P>0.10) was observed for Mn source × level inter- actions on the concentration of Cu, Mn, and Zn in the liver. Manganese concentration increased (linear,P= 0.015) as added Mn increased and liver Mn tended to be greater (P = 0.075) when Mn was supplied by MnSO4compared to IBM. There was no evidence of difference (P>0.10) for Mn source or level influence on liver Cu and Zn concentrations. In conclusion, these data suggest little difference among Mn sources but did show improvements in growth performance for dietary levels of 8 and 32 ppm of Mn compared with 16 ppm. Further research is needed to understand why pigs fed the intermediate level of Mn had decreased ADG.
Keywords: finishing pig; growth performance; manganese